2016
DOI: 10.1242/jeb.141325
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress during courtship affects male and female reproductive effort differentially in a wild bird with biparental care

Abstract: Oxidative stress has been suggested as one of the physiological mechanisms modulating reproductive effort, including investment in mate choice. Here, we evaluated whether oxidative stress influences breeding decisions by acting as a cost of or constraint on reproduction in the brown booby (Sula leucogaster), a long-lived seabird with prolonged biparental care. We found that during courtship, levels of lipid peroxidation (LP) of males and females were positively associated with gular skin color, a trait presuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 100 publications
1
17
2
Order By: Relevance
“…Importantly, Webb et al (2018) measured this effect during vitellogenesis, thus pointing to this period as being key to understanding the relationship between reproductive investment and ROM production. A similar pattern of higher reactive oxygen metabolite production earlier in the reproductive cycle is also found in snakes (Antaresia childreni, Stahlschmidt et al, 2013) and birds (Sula leucogaster, Montoya et al, 2016). Our results agree with this pattern, whereby ROMs decreased during the gestation period, indicating that such potentially harmful by-products are greatest earlier in the reproductive process.…”
Section: Maternal Physiology and Reproductionsupporting
confidence: 89%
“…Importantly, Webb et al (2018) measured this effect during vitellogenesis, thus pointing to this period as being key to understanding the relationship between reproductive investment and ROM production. A similar pattern of higher reactive oxygen metabolite production earlier in the reproductive cycle is also found in snakes (Antaresia childreni, Stahlschmidt et al, 2013) and birds (Sula leucogaster, Montoya et al, 2016). Our results agree with this pattern, whereby ROMs decreased during the gestation period, indicating that such potentially harmful by-products are greatest earlier in the reproductive process.…”
Section: Maternal Physiology and Reproductionsupporting
confidence: 89%
“…Nevertheless, Merkling et al (2017) concluded that 'only individuals that could afford to invest heavily in reproduction did so'. Montoya et al (2016) reported that reactive oxygen species levels during courtship were not associated with subsequent provisioning effort, time attending offspring, or chick growth, but mothers with higher pre-laying lipid peroxidation spent less time attending their chicks even though they provisioned chicks at the same rate. These studies provide very limited support for the idea that baseline physiological state, measured at a time when parents are not involved in intense, demanding activity (e.g.…”
Section: Cost Of Reproductionmentioning
confidence: 99%
“…1B). To my knowledge, few studies have approached the issue of costs of reproduction from this perspectivedoes an individual's physiological state either before reproduction or during early breeding stages influence its subsequent reproductive effort, workload ability or fitness (but see Merkling et al, 2017;Montoya et al, 2016;below)? This contrasts with the standard view that reproductive effort itself influences an individual's physiological state at the end of the breeding season.…”
Section: Cost Of Reproductionmentioning
confidence: 99%
“…Reproduction is an energetically expensive process for females, increasing resource requirements, metabolism (Angilletta & Sears, ) and potentially the production of ROS (Costantini, ,b; Metcalfe & Alonso‐Alvarez, ; Metcalfe & Monaghan, ). Oxidative costs of reproduction have been demonstrated in females of numerous species, including wild Song Sparrows ( Melospiza melodia ) (Travers, Clinchy, Zanette, Boonstra, & Williams, ), the viviparous Asp Viper ( Vipera aspis ) (Stier et al., ), Brown Boobies ( Sula leucogaster ) (Montoya, Valverde, Rojas, & Torres, ), Zebra Finches ( Taeniopygia guttata ) (Noguera, ) and White‐Browed Sparrow‐Weavers ( Plocepasse mahali ) (Cram, Blount, & Young, ). However, reproduction is a series of physiological events, and different stages have varying energetic demands; it is likely that oxidative stress also varies with reproductive stage.…”
Section: Introductionmentioning
confidence: 99%